Electrochemical immunoassay for the detection of antibodies to tick-borne encephalitis virus by using various types of bioconjugates based on silver nanoparticles - Khristunova, Ekaterina; Barek, Jiri; Kratochvil, Bohumil; Korotkova, Elena; Dorozhko, Elena; Vyskocil, Vlastimil (Bioelectrochemistry, 2020)
This work reports for the first time a significantly improved and simplified electrochemical immunoassay to detect antibodies to tick-borne encephalitis virus (TBEV) using a 96-well microtiter plate as a platform for immobilization and silver nanoparticles (AgNPs) as electrochemical labels. The electrochemical assay is performed by detecting the elemental silver oxidation signal where the electroactive signalling silver species are released from the bioconjugates (Ab@AgNP, AbS@AgNP, and ProteinA@AgNP). For this purpose, AgNPs were synthesized and further tagged with biomolecules (antibodies to TBEV, cleaved antibodies to TBEV, and protein A). Signal is read by linear sweep anodic stripping voltammetry (LSASV) of silver ions (through the electrochemical stripping of accumulated elemental silver) on a graphite electrode (GE). AbS@AgNP was chosen as the best option for the new electrochemical immunoassay. The results of electrochemical measurements demonstrated that voltammetric signal increased with the increasing concentration of target antibodies to TBEV within the range from 100 to 1600 IU mL-1, with a detection limit of 90 IU mL-1. To verify the practical application of the novel electrochemical immunosensor, the quantity of immunoglobulins against TBEV in human serum was checked. The results may contribute to the development of alternative methods for monitoring TBEV in biological fluids.
Keywords: Antibodies, Viral; viry klíšťové encefalitidy; Encephalitis Viruses, Tick-Borne; stříbro; Electrochemical Techniques; lidé; kovové nanočástice; Metal Nanoparticles; Immunoassay; Silver; Encephalitis, Tick-Borne; klíšťová encefalitida; imunoanalýza; Humans; protilátky virové; elektrochemické techniky